Genetic and epigenetic changes of GPX1 and GPX3 in human clear-cell renal cell carcinoma - Rudenko, E.E.; Gerashchenko, G.V.; Lapska, Y.V.; Bogatyrova, O.O.; Vozianov, S.O.; Zgonnyk, Y.M.; Kashuba, V.I. (Вiopolymers and Cell, 2013)
Aim. To find putative diagnostic and prognostic markers of cancerogenesis. Methods. Analysis of microarray and SAGE data, quantitative PCR (Q-PCR), bisulfite sequencing, methylation-specific PCR. Results. Bioinformatic analysis of microarray and SAGE database revealed that genes, encoding the glutathione peroxidase 1 and 3 (GPX1 and GPX3) were expressed at low levels in renal cancers. The relative gene expression of GPX1 and GPX3 that was widely inactivated in clear-cell renal cell carcinoma (ccRCC) was confirmed by Q-PCR. No correlation between expression levels and promoter methylation was found. It was found, however, that an allele with five ALA repeats in the N-terminal region of GPX1 is the most frequent polymorphic variant in ccRCC patients. Conclusions. Our data support the hypothesis that GPX1 and GPX3 are involved in tumorigenesis of ccRCC and could be putative TSGs (tumor suppressor genes) in renal cancer.